Geometric morphometric analysis applied to theropod tracks from the Lower Cretaceous (Berriasian) of Spain. (27th October 2014) - Castanera, Diego; Colmenar, Jorge; Sauqué, Víctor; Canudo, José I.; Benson, Roger
Abstract Geometric morphometric methods applied to theropod tracks from the Huérteles Formation (Berriasian, Spain) are here shown to be invaluable for drawing comparisons between theropod tracks with different preservation modes (true tracks, shallow undertracks and natural casts) or differing in the preservation of anatomical features (e.g. digital pads). Principal components analysis and thin‐plate spline methods can quantitatively distinguish between the broad groups of tracks in a sample and establish the main differences between them. These methods offer a promising approach for estimating ichnodiversity, achieved by evaluating just the morphology of the tracks independent of other factors such as size. The theropod tracks of the Huérteles Formation can be classified into two broad groups: minute‐to‐medium‐sized gracile theropod tracks (Kalohipus bretunensis) and medium‐to‐large‐sized robust theropod tracks (Iberosauripus). The presence of a third group of more gracile medium‐to‐large‐sized theropod tracks (Megalosauripus) cannot be proven with certainty on the basis of the current data. These results indicate that the theropod ichnodiversity of the Huérteles Formation is probably lower than that estimated by means of conventional methods alone (e.g. qualitative description of the tracks) and that many of the described theropod morphotypes may represent extramorphological or ontogenetic variations of other morphotypes.